2017
DOI: 10.1016/j.jad.2017.03.063
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial magnetic stimulation for treatment-resistant depression: Naturalistic treatment outcomes for younger versus older patients

Abstract: Background Repetitive transcranial magnetic stimulation (TMS) has been shown to be safe and effective for treatment-resistant depression (TRD) in the general adult population. Efficacy among older (≥60 years) patients, who have a greater burden of cognitive, physical, and functional impairment compared to their younger counterparts, remains unclear. The current study aimed to characterize antidepressant response to an acute course of TMS therapy among patients aged ≥60 years compared to those < 60 years in nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 29 publications
(44 reference statements)
2
23
0
Order By: Relevance
“…Prior TMS studies indicated that older age was associated with poorer response (Figiel et al, 1998;Manes et al, 2001;Mosimann et al, 2002Mosimann et al, , 2004Su, Huang, & Wei, 2005; but also see Conelea et al, 2017 Limitations of this study are those inherent to a follow-up, exploratory evaluation of a multisite clinical efficacy study. In that study, there was a modest range of demographic features and level of antidepressant resistance that may have limited our ability to detect other clinically significant predictors of response.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Prior TMS studies indicated that older age was associated with poorer response (Figiel et al, 1998;Manes et al, 2001;Mosimann et al, 2002Mosimann et al, , 2004Su, Huang, & Wei, 2005; but also see Conelea et al, 2017 Limitations of this study are those inherent to a follow-up, exploratory evaluation of a multisite clinical efficacy study. In that study, there was a modest range of demographic features and level of antidepressant resistance that may have limited our ability to detect other clinically significant predictors of response.…”
Section: Discussionmentioning
confidence: 83%
“…Several predictors of response did not emerge from our analysis. Prior TMS studies indicated that older age was associated with poorer response (Figiel et al., ; Manes et al., ; Mosimann et al., , ; Su, Huang, & Wei, ; but also see Conelea et al., ). This age result was not replicated in the Lisanby et al.…”
Section: Discussionmentioning
confidence: 97%
“…The question as to whether age can be used as a predictor to the e cacy of rTMS is one of the topics ercely debated in recent years. On one hand, initial RCTs indicate that old age may be a poor predictor of the response to rTMS, with lower response rate in elderly patients [45,46], of which this conclusion is not supported by meta-analyses and recent report [48][49][50]. On the other hand, advanced age has been shown to correlate with better response to rTMS [50,51].…”
Section: Discussionmentioning
confidence: 98%
“…Patient age has been of much interest within the rTMS treatment literature and investigations into the relationship between age and rTMS efficacy have largely produced mixed results. A number of rTMS studies have found support for the notion that rTMS may be less effective for depression in older individuals (e.g., [5,[14][15][16]), while others have not found age to be a significant predictor of rTMS outcomes (e.g., [6,7,17,18]). At least one group has found the relationship between age and rTMS outcome to be curvilinear [19].…”
Section: Demographic and Clinical Characteristicsmentioning
confidence: 99%